Hard to Manage? Dynamics of Soft-Shell Crab in the Newfoundland and Labrador Snow Crab Fishery - Mullowney, Darrell R.J.; Baker, Krista D.; Pantin, Julia R. (Frontiers in Marine Science, 2021)
Capture of recently molted soft-shell crab in the Newfoundland and Labrador (NL) snow crab (Chionoecetes opilio) fishery is undesirable due to resource wastage associated with low meat yield and supposed high mortality rates upon discard. This study is intended to formalize best-practice management advice for avoidance of soft-shell crab in the fishery. The study investigates factors affecting soft-shell incidence in the catch across a large geographic stock range encompassing dynamic habitat and contrasting harvest rate strategies. The results demonstrate an interaction between seasonality and harvest rate in governing soft-shell crab levels in the fishery. Greatest potential for high soft-shell incidence occurs in late-spring or summer (June-July) fisheries in warm water populations subjected to heavy fishing pressure, with warm water populations shown to be associated with earlier molting periods. The study concludes that the optimal time to harvest snow crab is during winter or early spring, and advises that wherever winter or early spring fisheries are not possible, a best-practice management strategy is to minimize wastage by maintaining a strong residual biomass of large hard-shell males in the population at all times. This strategy is easily enabled by consistent application of low exploitation rates. crab resource is to maintain low fisheries exploitation rates and a high residual biomass of large hard-shell males in the population at all times toward minimizing resource wastage. Finally, the study concludes that controls instituted to monitor soft-shell crab in the NL snow crab fishery are inadequate to safeguard against discard mortality and address management objectives.